ByzRev 05.2023.008: Enrico E. Prodi (ed.), Τζετζικαὶ ἔρευναι. : (Eikasmos. Studi di Eikasmos online 4). Bologna: Pàtron Editore 2022. xxxv, 481 pp. - van den Berg, Baukje (The Byzantine Review, 2023)
Enrico E. Prodi (ed.), Τζετζικαὶ ἔρευναι. (Eikasmos. Studi di Eikasmos online 4). Bologna: Pàtron Editore 2022. xxxv, 481 pp. – ISBN 978-88-5558001-4. Open Access: https://bit.ly/3ZKnkEc